2016
DOI: 10.1002/pmic.201500349
|View full text |Cite|
|
Sign up to set email alerts
|

Exome-based proteogenomics of HEK-293 human cell line: Coding genomic variants identified at the level of shotgun proteome

Abstract: Genomic and proteomic data were integrated into the proteogenomic workflow to identify coding genomic variants of Human Embryonic Kidney 293 (HEK-293) cell line at the proteome level. Shotgun proteome data published by Geiger et al. (2012), Chick et al. (2015), and obtained in this work for HEK-293 were searched against the customized genomic database generated using exome data published by Lin et al. (2014). Overall, 112 unique variants were identified at the proteome level out of ∼1200 coding variants annota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 36 publications
6
49
0
1
Order By: Relevance
“…Manual inspection of the mass spectra of variant peptides was also performed for expert validation of findings as suggested recently . As one of the striking results obtained for the murine data, an edited peptide VTIAQGGVLP S IQAVLLPK with one acetylation site from the common histone HIST2H2AC was reported with high spectral counts.…”
Section: Resultsmentioning
confidence: 99%
“…Manual inspection of the mass spectra of variant peptides was also performed for expert validation of findings as suggested recently . As one of the striking results obtained for the murine data, an edited peptide VTIAQGGVLP S IQAVLLPK with one acetylation site from the common histone HIST2H2AC was reported with high spectral counts.…”
Section: Resultsmentioning
confidence: 99%
“…Such variants may be deleterious, and their deleteriousness can be predicted from the evolutionary conservation of homologous sequences or the structures of the encoded proteins . The sequences for such genome‐encoded variants can be obtained from exome sequencing, RNA‐Seq, or existing SNP/SNV databases. In a C‐HPP study on chromosome‐9, LC‐MS/MS and RNA‐Seq were performed on five pairs of lung adenocarcinoma tumors and adjacent non‐tumor tissues, resulting in the identification of seven unique SNPs; and four missense mutations in proteins such as LTF, HDLBP, TF, and HBD in the tumor samples .…”
Section: Applications Of Proteogenomics In Biologymentioning
confidence: 99%
“…Such proteogenomic studies have helped to identify novel genes, splice variants, N-terminal extensions, alternative open reading frames, and short proteins in the genomes of both well-characterized and less-studied organisms [1]. Despite the initial excitement, most studies identified only a few hundred new proteins or protein variants: ~100 in the model cell line HEK-293 [28], ~300 in grapevine and monkey [29,30], ~600 in pig [31], and >800 in mosquito [32]. These relatively low numbers may be due to the limited genome coverage that proteomics provides or its bias towards high-abundance proteins, though it may also indicate that the predictive algorithms capture most of the variation, at least within the known feature space.…”
Section: Expanding the Annotation Of Genomesmentioning
confidence: 99%